Penguatan ekonomi kreatif berbasis potensi sumber daya desa pada masyarakat Desa Kaliang Kecamatan Duampanua Kabupaten Pinrang - Chalid Imran Musa; W. Kristina Parinsi; Rusman Rasyid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) is the people of Kaliang Village. The problem is: (1) The low level of community knowledge in identifying potential village resources that can be utilized in supporting the creative economy for the purpose of improving welfare (2) The low motivation of the community to increase their income through optimizing the use of village resources. (3) The low access for information, technology, skills training and network marketing of the results of their businesses. The external target is to strengthen the creative economy based on village resources in the Kaliang village community. The method used is: lecture, demonstration, discussion, question and answer, and observation. The results achieved are 1) The partners have knowledge in identifying the potential of village resources that can be utilized in supporting the creative economy for the purpose of improving welfare (2) The partners have the motivation to increase their income through optimizing the use of village resources. (3) The Partners have access to information, technology, skills training and marketing networks of their business results.